Synthesis of Nanocrystalline Yttria Stabilized Zirconia for SOFC - Mridula Biswas; Prasant Kumar Ojha; E. Moses Jayasingh; C. Durga Prasad (Nanomaterials and Nanotechnology)
Nanocrystalline zirconia powders stabilized with varying concentration of yttria (YSZ) were synthesized following urea solution combustion route. Thermogravimetric analysis combined with differential scanning calorimetry was carried out for the intermediate gel for analyzing reaction kinetics. The final products were characterized by X‐ray diffractometry, transmission electron microscopy and specific surface area measurements. Sintering behavior of theses powders were studied. The powder quality is poor in respect of surface area and sintered density.